Italy : Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2013)
This paper elaborates key findings of the Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision by Italy. The core supervisory process at the Banca d'Italia (BI) is strong, and it has a well-defined and integrated supervisory approach. BI is well regarded both in terms of independence, professional qualification, and integrity. The various components of its supervision are integrated in the Supervisory Review and Evaluation Process. The authorities have made progress in addressing the recommendations of the 2006 Financial Sector Assessment Program, although some issues remain. The supervisory coverage of the Bank of Italy is comprehensive, and the follow-up process is intensive.